The independent piano teacher's studio handbook : everything you need to know for a successful teaching studio - Klingenstein, Beth Gigante (Milwaukee, WI : Hal Leonard, 2009)
Synopsis: This handy and thorough guide is designed to help the independent piano teacher in all aspects of running his/her own studio. Whether it be business practices such as payment plans, taxes, and marketing, or teaching tips involving technique, composition, or sight reading, this all-inclusive manual has it all! Topics include: Developing and Maintaining a Professional Studio, Finances, Establishing Lessons, Studio Recitals, Tuition and Payment Plans, Composition and Improvisation, Marketing, Communications with Parents, Make-up Policies, Zoning and Business Licenses, Teaching Materials and Learning Styles, The Art of Practice, Arts Funding, and many more!
-- Preface -- Acknowledgments -- Part 1: Development And Maintaining Professionalism In The Independent Piano Studio -- Chapter 1: Embracing professionalism -- Chapter 2: Professional studio documents -- Chapter 3: Setting up the ideal studio space -- Chapter 4: Office technology for the studio -- Part 2: Finances -- Chapter 5: Setting rates -- Chapter 6: Deeper look at tuition and payment plans -- Chapter 7: Marketing -- Chapter 8: Taxes, insurance, and retirement funds -- Part 3: Establishing Lessons -- Chapter 9: Interviews and communications with parents -- Chapter 10: Scheduling lessons -- Chapter 11: Make-up policies -- Part 5: Image -- Chapter 12: Public perceptions of the independent music teacher -- Chapter 13: Clarifying image: the of teacher surveys -- Chapter 14: Projecting a professional image -- Part 5: Zoning Laws And Ethical Issues -- Chapter 15: Zoning and business licenses -- Chapter 16: Ethics in teaching -- Part 6: Maintaining High Studio Standards -- Chapter 17: Studio atmosphere -- Chapter 18: Teaching materials and leaning styles -- Chapter 19: Professional development, professional organizations, and partnerships -- Chapter 20: Teacher certification through professional organizations -- Part 7: From Preparation To Performance -- Chapter 21: Art of practice -- Chapter 22: Art of memorization -- Chapter 23: Art of performance -- Chapter 24: Studio recitals -- Chapter 25: Additional performance, assessment, and testing opportunities -- Part 8: Teaching Skills-Not Pieces -- Chapter Timing and rhythm -- Chapter 27: Technique -- Chapter 28: Sight-playing -- Chapter 29: Fingering -- Chapter 30: Pedaling -- Chapter 31: Developing the ear -- Part 9: Unique Curriculum -- Chapter 32: Embracing national standards in studio teaching -- Chapter 33: Music history and performance styles -- Chapter 34: Music theory and harmony -- Chapter 35: Collaborative arts -- Chapter 36: Composition -- Chapter 37: Jazz, blues, and improvisation -- Chapter 38: Music of many cultures -- Chapter 39: Music camps -- Chapter 40: Workstations -- Chapter 41: Additional teaching options -- Part 10: Technology -- Chapter 42: Equipment -- Chapter 43: Studio uses for technology -- Part 11: Careers In Music -- Chapter 44: Performance -- Chapter 45: Composing and arranging -- Chapter 46: Education -- Chapter 47: Service -- Chapter 48: Business -- Part 12: Broader Picture -- Chapter 49: Arts funding -- Chapter 50: Arts advocacy -- Appendix A: Studio documents -- Appendix B: Sample survey -- Appendix C: Professional organizations -- Index.
Includes resources and websites (at the end of each chapter), and index.
Keywords: Piano teachers -- Vocational guidance -- Handbooks, manuals, etc; Music trade -- Vocational guidance -- Handbooks, manuals, etc; Music -- Economic aspects